2023
DOI: 10.3390/fermentation9050408
|View full text |Cite
|
Sign up to set email alerts
|

Attributes of Lactobacillus acidophilus as Effected by Carao (Cassia grandis) Pulp Powder

Abstract: This study aimed to examine the prebiotic effect of Carao (Cassia grandis) pulp powder on the probiotic characteristics of Lactobacillus acidophilus regarding the viability, enzymatic activity, lysozyme resistance, bile and acid tolerances, and tolerance to gastric juices. Carao powder was used at 0% (control), 1%, 2%, and 3% (w/v). Acid and lysozyme tolerance were determined at 0, 30, 60, 90, and 120 min of incubation, whereas bile tolerance was analyzed at 0, 4, and 8 h. The gastric juice tolerance was deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Targeted functional ingredients are desired for delivery in cells, tissues and organs via local or systemic blood circulation, allowing the ingredients to act directly on the targeted illness sites and, therefore, more effectively generate remedial effects. The literature reports that the Cassia grandis has shown probiotic characteristics towards L. acidophilus [18]. Medical plants have also shown immuno-stimulant effects in albino rats with aqueous and methanolic extracts [30].…”
Section: Impact Of Carao Fortified Yogurt Diet On Body and Relative O...mentioning
confidence: 99%
See 2 more Smart Citations
“…Targeted functional ingredients are desired for delivery in cells, tissues and organs via local or systemic blood circulation, allowing the ingredients to act directly on the targeted illness sites and, therefore, more effectively generate remedial effects. The literature reports that the Cassia grandis has shown probiotic characteristics towards L. acidophilus [18]. Medical plants have also shown immuno-stimulant effects in albino rats with aqueous and methanolic extracts [30].…”
Section: Impact Of Carao Fortified Yogurt Diet On Body and Relative O...mentioning
confidence: 99%
“…Paz et al (2022) [17] and Fuentes et al (2023) [18] indicated that carao improved the acid and bile tolerance of Streptococcus thermophilus, Lactobacillus delbrueckii ssp. bulgaricus, and Lactobacillus acidophilus [17,18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other treatments (pulp and crust) indicated the same LB counts at the end of the experiment. [32] examined the lysozyme tolerance of L. acidophilus and concluded that carao pulp improved growth. Lysozyme is a natural enzyme that acts as a [32] examined the lysozyme tolerance of L. acidophilus and concluded that carao pulp improved growth.…”
Section: Resistance To Lysozymementioning
confidence: 99%
“…Carao is also known for its pharmaceutical properties due to the presence of lanthanoids with strong laxative and antibacterial effects [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%